2009
DOI: 10.1111/j.1439-0396.2009.00921_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and therapeutic efficacy of undenatured type‐ii collagen (UC‐II) in comparison to glucosamine and chondroitin in arthritic horses

Abstract: antioxidant potential, therefore justifying a larger study with antioxidant supplementation to determine how antioxidants in weight loss diets effects endogenous antioxidant capabilities.Safety and therapeutic efficacy of undenatured type-ii collagen (UC-II) in comparison to glucosamine and chondroitin in arthritic horses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Previous research has shown undenatured type II collagen supplementation to improve knee extension range of motion in healthy individuals with exercise-induced knee pain [9]. Similar bene ts have been reported in animal studies, with both arthritic dogs [10] and arthritic horses [11] showing reduced pain during joint manipulation following supplementation periods with undenatured type II collagen.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous research has shown undenatured type II collagen supplementation to improve knee extension range of motion in healthy individuals with exercise-induced knee pain [9]. Similar bene ts have been reported in animal studies, with both arthritic dogs [10] and arthritic horses [11] showing reduced pain during joint manipulation following supplementation periods with undenatured type II collagen.…”
Section: Introductionsupporting
confidence: 57%
“…UC-II® is a unique nutritional supplement that has demonstrated support for joint health in humans [9] and animals [10,11]. In the current report, daily supplementation (40mg) of undenatured type II collagen for 120 days prompted signi cant improvements in KOOS survey scores compared to placebo in a cohort…”
Section: Discussionmentioning
confidence: 87%